2009
DOI: 10.4103/0973-6247.45259
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhemolysis in a patient with β-thalassemia major

Abstract: A case of hyperhemolysis in a 2-year-old boy with β thalassemia major was noted. After several transfusions, he developed hyperhemolysis with a positive (C3d only) direct antiglobulin test (DAT) and no clinically significant RBC allo- or auto-antibodies. (There was a weak cold antibody, showing a narrow thermal range). Because there was no significant improvement with steroid and immunoglobulin infusions, cyclophosphamide therapy was tried with notable success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…They discuss that IgA may lyse RBCs while common serologic tests are negative. They explain that ADCC may occur with low level of antibodies that were not detectable by serologic tests [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They discuss that IgA may lyse RBCs while common serologic tests are negative. They explain that ADCC may occur with low level of antibodies that were not detectable by serologic tests [4].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of HLA antibodies and RBC alloantibodies, it is suggested that macrophages are involved in RBCs destruction [10]. Morawakage et al (2009) reported a case of HS in a child with thalassemia with 2+ DAT for C3b but they could not find any antibody in the patient's serum. They discuss that IgA may lyse RBCs while common serologic tests are negative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note reticulocytopenia is also present, in contrast to other types of hemolytic reactions, where reticulocytosis is usually notable 4. HHTR most commonly occurs in patients with sickle cell disease,2,3,5 while occasionally it has been reported in patients with thalassemia4,6,7 and in individuals without underlying hematologic diseases 8,9…”
Section: Introductionmentioning
confidence: 99%